Optimization of Hybrid Bentonite for Mechanical Properties of Green Sand Mould - Modi, Arpit H.; Acharya, Shailee G. (Archives of Foundry Engineering, 2026)
Aim – As green sand moulding is the cheapest, fastest, and most commonly used method for metal casting process this research aims to optimize the hybrid bentonite for the mechanical properties of green sand mould which leads to a better-quality of casting and reduction in rework. Materials – For the experiments green sand was prepared by mixing reclaimed sand, garcolap powder, hybrid bentonite and water. Hybrid bentonite is a mixture of bentonite (pure sodium bentonite containing more than 75% montmorillonite) and clay (bentonite clay having 40-55% montmorillonite). Experiments/Methodology/Approach – Experimental results were optimized using Minitab software version 21 to find out values of bentonite, garcolap powder and water to be kept constant for experiments to optimize hybrid bentonite. In this research work mechanical properties of green sand like compactibility, permeability, mould hardness (MH), green compressive strength (GCS) and moisture content were measured for the experiments performed on specimen prepared from green sand in accordance with the IS: 1918-1966. Findings – Experiments performed to optimize hybrid bentonite suggests best combine values of process parameters for hybrid bentonite with 85/15 ratio. Research limitations/Implications – Hybrid bentonite composition optimized in this research can be applied to prepare hybrid bentonite for other casting industries only if the chemical composition of bentonite is approximately same as used in current work. If chemical composition of bentonite gets changed then researcher has to apply same methodology to find new composition of hybrid bentonite for their green sand moulding process.